PEMETAAN MUATAN PADATAN TERSUSPENSI MENGGUNAKAN DATA SATELIT LANDSAT (STUDI KASUS: TELUK SEMANGKA) (TOTAL SUSPENDED MATTER MAPPING USING LANDSAT SATELLITE DATA (CASE STUDY: SEMANGKA GULF)) - Muchlisin Arief (Indonesian National Institute of Aeronautics and Space (LAPAN), 2012)
Total Suspended Matters (TSM) defined all solids or particles with a larger size 1 μm that are suspended in water resulting in decreased quality of water until the water can not be used as intended. There are various methods that have been made in mapping the TSM based on remote sensing satellite data both low and high resolution. This paper describes TSM mapping which TSM algorithm was directly applied to the digital number value of Landsat image. The mapping process was preceded by a thresholding method to separate the water with other objects (clouds, cloud shadows and the mainland), then the TSM concentration was calculated through the algebraic sum of band1, 2.3, and 4 and ended with density slice range process. Based on the TSM analysis, the TSM concentration in the Semangka Gulf was caused by human waste and also the material carried by streams of water from ponds and sewage waste soil erosion. TSM concentration areas was spread out in water of the Wonosobo District until 640 meters of spreading length and Kota Agung Timur districts until 3240 meters of spreading length. Key words: Total Suspended Matter, Semangka gulf, Thresholding